2004
DOI: 10.1029/2003jc001856
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coastal upwelling and El Niño–Southern Oscillation on nearshore water along Baja California and Chile: Shore‐based monitoring during 1997–2000

Abstract: [1] In order to determine the sensitivity of coastal upwelling tracers to seasonal wind forcing and El Niño-Southern Oscillation (ENSO) off Baja California and Chile, nearshore salinity, cadmium (Cd), and nutrients phosphate, silicate, nitrate+nitrite were monitored in surf zone waters at six locations along the North and South American coasts during 1997-2000. The clearest responses to upwelling favorable wind forcing were observed at the southern tip of Baja California (23.3°N) and off central-southern Chile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 65 publications
2
36
0
7
Order By: Relevance
“…Variations in the strength of the OMZ are probably important to determine solid phase P dynamics in the study area. This conclusion is in agreement with observations made by Takesue et al (2004) who found that the ratio Cd/P in upwelled waters during spring-early summer in Coliumo Bay (central Chile) was lower than expected (0.27 × 10 -3 mmol mol -1 ) compared to the California upwelling system (0.35 × 10 -3 mmol mol -1 ). These authors suggested that the proportion of Cd:P in upwelling waters could be altered when surface sediments are anoxic since Cd precipitates into pore waters as a sulfide and P is released from sediments.…”
Section: Solid Phase Phosphorus and Oxygen Minimum Zone Fluctuationssupporting
confidence: 82%
“…Variations in the strength of the OMZ are probably important to determine solid phase P dynamics in the study area. This conclusion is in agreement with observations made by Takesue et al (2004) who found that the ratio Cd/P in upwelled waters during spring-early summer in Coliumo Bay (central Chile) was lower than expected (0.27 × 10 -3 mmol mol -1 ) compared to the California upwelling system (0.35 × 10 -3 mmol mol -1 ). These authors suggested that the proportion of Cd:P in upwelling waters could be altered when surface sediments are anoxic since Cd precipitates into pore waters as a sulfide and P is released from sediments.…”
Section: Solid Phase Phosphorus and Oxygen Minimum Zone Fluctuationssupporting
confidence: 82%
“…The main upwelling area is located at a distance of approximately 40 km southwest of the study area (Acuña et al 1989). The main subsurface source of upwelling off northern Chile is the subsurface equatorial water (Morales et al 1996), which is characterized as being relatively cold, oxygen-poor water, with a high nutrient content (Silva & Konow 1975), leading to the high productivity of this coastal region (Acuña et al 1989, Daneri et al 2000, Takesue et al 2004.…”
Section: Methodsmentioning
confidence: 99%
“…Uno de ellos es la variación espacial en ocurrencia, frecuencia e intensidad de la surgencia costera, con efectos diferenciales entre especies, niveles tróficos, grupos funcionales o ensambles locales (e.g., Moreno et al 1998, Vásquez et al 1998, Camus & Andrade 1999, Broitman et al 2001, Nielsen & Navarrete 2004, Lagos et al 2005, Wieters 2005, Lagos et al 2008. Otro es El Niño-Oscilación del Sur, que afecta diferencialmente la riqueza, abundancia y composición de las comunidades del intermareal rocoso, pero a su vez puede modificar la frecuencia e intensidad de la surgencia (e.g., Camus & Ojeda 1992, Castilla & Camus 1992, Camus 1994, Moreno et al 1998, Takesue et al 2004, Thiel et al 2007. Datos recientes de la composición de cuatro ensambles intermareales del norte de Chile entre 21º y 30ºS, muestran que su nivel de recambio de especies es muy alto en espacio (46-57% entre pares de ensambles, media ~50%; Camus, datos no publicados) y tiempo (promedio estacional ~40-50% en cada ensamble; Camus 2008), lo cual podría ser una característica de las comunidades en esta región.…”
Section: Introductionunclassified